Designing A Computer Network Monitoring System With Sms Notification Using The Dude - Riki Irawansyah; Khairil Khairil; Rizka Tri Alinse (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
One system that can monitor networks with notifications in the form of SMS is using The Dude. This network monitoring system with SMS Notification aims to enable network admins to know the condition of the network wherever they are.In monitoring the network, the dude can do it based on the IP address entered, the dude is open source, that is, it is one of the software or tools built into the proxy, in the installation process the dude does not require a large storage space. When monitoring the Dude's network, the indicator will display green, which is on and red, which is off. To monitor the Dude's network, it will be based on the IP Address of each device connected to the network.The Dude can carry out network monitoring on the SMA N 6 South Bengkulu computer network in the form of notifications of devices being on or off. The results of the monitoring will be sent in the form of a notification to the admin's cellphone in the form of an SMS. To send an SMS notification, the dude takes +/- 2 minutes. The time for sending this SMS notification is calculated based on the condition of the device being on or off until the notification is received or received. on HP.